PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS INTERNET BAGI GURU BIOLOGI SMA DI KABUPATEN SLEMAN - Hinuhili, dkk, Victoria (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
AbstractInformation technology has progressed rapidly. The using of informationtechnology can help teachers to manage their time for searchingreferences that can be useful to teach their students. This programme wasaimed to give a course for biology teachers of Senior High Schools atSleman District to use information technology for making lessoning mediabased on internet.The methode of this course was learning by doing. The team gavethe theory about information technology using for media making, and thenthe participants practiced it directly. There were 16 teacher participants fromSleman District, and one teacher from East Kalimantan as a guest teacher.The participants were very eager to search the information relatedtheir teaching tasks. They did searching, browsing, downloading, anduploading the information from internet and then they arranged it in alessoning media. In a limited trying test, lessoning media created by theparticipants could help the teaching-learning process clearly, but it neededtime more to prepare and to arrange the media.Keywords: lessoning media and internet